Local Wisdom Tourism: Optimizing the Role of Odong-Odong as a Means of Transportation in Kebumen Regency - Octanisa, Dheanita Sekarini (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to explore and analyze the role of Odong-odong as a means of tourist transportation in Kebumen Regency. The research method used is a qualitative approach with in-depth interviews with relevant stakeholders, as well as relevant literature studies. The results showed that Odong-odong has great potential in increasing tourism visits in Kebumen Regency. The use of Odong-odong provides a unique and enjoyable experience for tourists, especially families with children. Based on the results of the study, the author recommends several strategies to increase the role of Odong-odong as a means of tourist transportation in Kebumen Regency. These recommendations include improving the quality and variety of Odong-odong, providing a special path for Odong-odong, and promotion through social media. In the discussion, research findings were discussed compared to previous research and their relevance to tourism development where the use of odong - odong as tourist transportation can facilitate the access of tourists to the intended tourist destination